A cognitive framework for understanding development of the ability to deceive. (August 2019) - Walczyk, Jeffrey J.; Fargerson, Caroline
Abstract: A large research literature shows how the ability to deceive improves from early childhood on. For instance, growth in Theory of Mind allows older children to infer accurately others' mental states, enabling plausible lying. However, theoretical frameworks for integrating these findings are scarce. We expand a cognitive theory of adult high-stakes deception for this purpose: Activation-Decision-Construction-Action Theory (ADCAT). According to ADCAT, deception typically involves four components: activation of the truth, a decision to lie if sharing the truth is sufficiently negative and if conveying a deception is sufficiently positive, construction of a lie that achieves goals, and then acting the deception out. Each component is elaborated developmentally, predictions are generated, and possible tests are proposed. The core developmental principle is that with age deceivers will discover more effective ways to reduce the cognitive load of deception. Expanded ADCAT organizes and explains many research findings and suggests dimensions for understanding deception development throughout the lifespan.